ByzRev 07.2025.001: Michael Edward Stewart – David Alan Parnell – Conor Whately (eds), The Routledge Handbook on Identity in Byzantium.: Abingdon – New York: Routledge 2022. - Holmes, Catherine (The Byzantine Review, 2025)
Michael Edward Stewart – David Alan Parnell – Conor Whately (eds), The Routledge Handbook on Identity in Byzantium. Abingdon – New York: Routledge 2022. xiv, 453 pp. – ISBN 978-0-367-14341-1